Disassembly of the Staphylococcus aureus hibernating 100S ribosome by an evolutionarily conserved GTPase - Basu, Arnab (Proc Natl Acad Sci U S A, 2017)
The bacterial hibernating 100S ribosome is a poorly understood form of the dimeric 70S particle that has been linked to pathogenesis, translational repression, starvation responses, and ribosome turnover. In the opportunistic pathogen Staphylococcus aureus and most other bacteria, hibernation-promoting factor (HPF) homodimerizes the 70S ribosomes to form a translationally silent 100S complex. Conversely, the 100S ribosomes dissociate into subunits and are presumably recycled for new rounds of translation. The regulation and disassembly of the 100S ribosome are largely unknown because the temporal abundance of the 100S ribosome varies considerably among different bacterial phyla. Here, we identify a universally conserved GTPase (HflX) as a bona fide dissociation factor of the S. aureus 100S ribosome. The expression levels hpf and hflX are coregulated by general stress and stringent responses in a temperature-dependent manner. While all tested guanosine analogs stimulate the splitting activity of HflX on the 70S ribosome, only GTP can completely dissociate the 100S ribosome. Our results reveal the antagonistic relationship of HPF and HflX and uncover the key regulators of 70S and 100S ribosome homeostasis that are intimately associated with bacterial survival.